NIGHT DREAM MOTIF IN “ULYSSES” BY J. JOYCE, “MURPHY” BY S. BECKETT AND “THE THIRD POLICEMAN” BY F. O’BRIEN - Vasyliuk, Elizabeth (Літературний процес: методологія, імена, тенденції, 2019)
The article analyses the plot creation function of the night dream motif and explores the combination of the motifs of the night dream with thanathological motif in the novels. In “Ulysses” and “The Third Policeman” the night dream serves as display of the guilt of the protagonists: Stephen`s guilt towards his dead mother, Noman`s guilt towards dead Mathers. In “Ulysses”, the nightdream of Bloom attracts Stephen into the world of dreams, in “Murphy”, Murphy attracts his beloved Celia in his own world of melancholy and apathy, and in “The Third Policeman” Noman is pushed by his friend and murderer John Divney into afterlife. The reception of the “Ulysses” diambulist / noctambulist pair in “Murphy” and “The Third Policeman” has been identified: in “Ulysses” it is represented by diambulist Bloom and noctambulist Stephen, in “Murphy” it is represented by diambulist Neary and noctambulist Murphy, and in “The Third Policeman” — by diambulist de Selby and noctambulist Noman. The certain leading role of night dream in the plots of novels is defined: in “Ulysses” Bloom and Stephen’s communication takes place at night, dream “leads” the protagonist to a psychiatric hospital in “Murphy”, in “The Third Policeman” the dream of Noman creates deep connection between him, John Divney (the murderer) and Mathers, Noman`s victim; it creates the fiction space of the novel. The protagonists in “Murphy” and “The Third Policeman” have doubles: Murphy has a neighbor who replaces Murphy for Celia, Noman has Martin Finnucane. The diambulist patrons which replace the fathers of the protagonists in S. Beckett’s and F. O’Brien’s novels are parody of diambulist Bloom: in “Murphy” Neary has a panic fear to die at night, while Bloom considers death in dream as the best one, and in “The Third Policeman” de Selby arranges comic scientific experiments, spending thousands gallons of water to clean the air from an “unsanitary night”, in which the “water” Bloom is also parodied. The dream in “Ulysses” tends to a carnival, the dream in “Murphy” — to surrealism, and in “The Third Policeman” absurdity is represented through the prism of serialism, while implying phantasmagority of dream in “Ulysses”. DOI: https://doi.org/10.28925/2412-2475.2019.1313